MEDICAL TERMS AND THEIR TRANSLATION INTO ENGLISH: LINGUISTIC AND PRACTICAL CHALLENGES IN MEDICAL COMMUNICATION - Fayziyeva Ra’no Abdusamadovna (International Journal of Literature and Language Studies, 2026)
The translation of medical terminology into English plays a crucial role in international healthcare communication, medical education, scientific research, and clinical documentation. Due to globalization and the increasing exchange of medical information across countries, accurate translation of medical terms has become a significant linguistic and professional necessity. This article investigates the linguistic structure of medical terminology, the major challenges encountered during translation into English, and the strategies used to ensure semantic precision. The study applies qualitative analysis to selected medical terms originating from Latin, Greek, and Uzbek/Russian medical discourse. The findings demonstrate that successful medical translation requires not only linguistic competence but also profound medical knowledge and cultural awareness. The article concludes that standardized terminology and specialized translator training are essential for improving the quality of medical communication.